The Effect of Information Precision and Information Reliability on Manufacturer-Retailer Relationships - Kulp, Susan Cohen (The Accounting Review, 2002)
This study investigates the extent to which a retailer's willingness to share internal (sales and inventory) information with a manufacturer and the reliability of the information transmission between the retailer and the manufacturer affect the total supply-chain profits resulting from two alternative inventory management systems. I present analytical models of a traditional system and a Vendor Managed Inventory (VMI) system. The VMI system is a supply-chain management technique in which the retailer delegates its inventory decisions to, and shares its internal accounting information with, the manufacturer. With VMI, the parties aim to reduce inventory-related costs and increase supply-chain profits. The theoretical analysis indicates that the system that produces higher supply-chain profits depends on the extent to which the retailer reveals its internal accounting information to the manufacturer and the ability of the manufacturer to accurately receive and use this information in its decisions. Survey data corroborate the model's prediction that manufacturers are more likely to select VMI when retailers provide more precise sales and inventory (i.e., demand) information and when the manufacturers' systems ensure reliable transmission and receipt of this information. The study's results suggest that managerial accountants should consider the retailer's willingness to share sales and inventory information with the manufacturer and the manufacturer's ability to reliably transmit this information before implementing VMI systems.